Energy conservation for fatigue management in multiple sclerosis: a pilot randomized controlled trial. (January 2013) - García Jalón, E Guiomar; Lennon, Sheila; Peoples, Louise; Murphy, Sam; Lowe-Strong, Andrea
Objective: To develop and test the feasibility of an energy conservation programme to manage fatigue in multiple sclerosis. Design: A pilot randomized controlled trial. Setting: Community setting. Subjects: People with multiple sclerosis reporting fatigue. Interventions: An energy conservation programme was compared to a peer support group. Both interventions were delivered in group format with 2-hour sessions once a week for five weeks. Patients' views about the interventions were sought in discussion groups one week post intervention. Main measures: The primary feasibility outcomes were recruitment and adherence. Other outcome measures were the Fatigue Impact Scale, Fatigue Severity Scale, MS-Impact Scale-29, MS Self-efficacy Scale, Beck's Depression Scale-Fast Screen and Epworth Sleepiness Scale. Outcomes were administered at baseline, post intervention, 6-week and 3-month follow-up. Results: Almost 30% of the people approached to take part in the study did not commit to participation because of transport/time issues. Twenty-three patients took part in the study. Three patients dropped out, one reporting adverse effects. A power calculation indicated that a sample of 56 (28 per group) would be required for a main randomized controlled trial. Patients valued peer support and those in the energy conservation group described the programme as useful, but reported difficulties completing some practice activities. Conclusion: An energy conservation programme in the community is feasible and welcomed by people with multiple sclerosis. However, future research needs to consider longer follow-ups and practical issues to improve recruitment rate by accommodating to patients' needs.